ATTRIBUTION STYLES AS CORRELATES OF TECHNICAL DRAWING TASK-PERSISTENCE AND TECHNICAL COLLEGE STUDENTS’ PERFORMANCE - Jane Itohan Oviawe; Mohamed Nor Azhari Azman; Tee Tze Kiong; Oryngul S. Abilmazhinova (LPMPP Universitas Negeri Yogyakarta, 2021)
The technical drawing is a means of communicating between the designer and the manufacturers to bring ideas into reality by means of drafting. This study investigated attribution styles as collates of students’ technical drawing task-persistence and academic performance using correlational research design. The population for this study consisted of 864 students of year II and the sample study comprised of 150 (93 males and 57 females) randomly selected from six technical colleges in Edo State, Nigeria. Three instruments, the Academic Performance Attribution Style Questionnaire (APASQ), Technical Drawing Task-persistent Rating Scale (TDTPRS); and Technical Drawing Performance Test (TDPT) were developed and used for data collection. Cronbach Alpha reliability method was used to determine the reliability of the instruments and the results were obtained: SAASQ = .87; TDTPRS=.79; AND TDAT=.85. The findings of the study revealed that the technical drawing task-persistence of students was positively correlated by functional attribution style; and was negatively correlated by dysfunctional attribution style; functional attribution style positively correlated academic performance of students. Based on the findings of the study, it was recommended among others that technical drawing teachers should model and teach the students the right attribution style that will enhance their learning of technical drawing.